Storytelling Sebagai Strategi Bisnis Sosial Start-Up Ojek Syar’i Berbasis Aplikasi di Surabaya - Tri Siwi Agustina (Forum Inovasi Bisnis dan Manajemen, 2020)
Syarihub is a social business startup initiated by two young people in Surabaya which is engaged in application-based public service transportation. Conscious of challenging its predecessors like Gojek, Grab and Uber; Syarihub chose to serve only for women and children. Facing many tight business competition in the application-based and preaching-based public service transportation business; Syarihub management tries to be observant in formulating strategies. As a social business, storytelling is considered as the best way to share and convey social values. Stories represent experiences, telling stories coordinate the past and hopes for the future. The aim of this study is to determine whether storytelling is a proper promotional media for Syarihub as a social business and to find out the storytelling strategy that has been implemented by Syarihub, especially in facing challenges its flapping business wings. The study approaches used descriptive qualitative with primary data sources (interviews with the founder and manager of Syarihub) and secondary data used the study of literature from various posts made by Syarihub on websites, social media and media coverage published from 2015 to 2019. The results showed that storytelling is the most appropriate media for social business, and the storytelling strategy adopted by Syarihub came from data driven storytelling, Philanthropic storytelling, Customer-led storytelling and immersive story telling. As a result, it has met the principles of effective storytelling, called TRUTH (Topical, Relevant, Unusual , Trouble, Human).